The Ontogeny and Dietary Differences in Queen and Worker Castes of Honey Bee (Apis cerana cerana) - Chunyu Yang; Li Lei; Ying Wang; Baohua Xu; Zhenguo Liu (Insects)
The honey bee Apis cerana cerana (A. c. cerana), a subspecies of Apis cerana, is endemic in China and possesses a valuable ecological niche. Understanding the ways to protect this honey bee’s populations is crucial, but this topic has been understudied. For the efficient utilization of beekeeping and pollination, there is a need to explore its biology and management practices. In light of this, the current study was carried out to investigate the ontogeny and dietary differences in the queen and worker castes of the A. c. cerana honey bee. This article presents, supplemented by reference images, a detailed description of the life history of A. c. cerana queens and workers. Additionally, this study investigated the nutritional differences between royal jelly (RJ) and worker jelly (WJ) at various larval ages. The contents of the moisture, crude protein, and amino acids in RJ and WJ were determined via freeze drying, Kjeldahl nitrogen determination, and ultra-high performance liquid chromatography. The results highlight significant variations in the moisture content, crude protein concentration, and amino acid concentration between RJ and WJ. The results offer theoretical support for ex situ artificial rearing practices of A. c. cerana.